Atrial Fibrillation that required Cardioversion in the Post Anesthetic Recovery Unit in Ambulatory Surgery. A case report: Fibrilación Auricular que requirió Cardioversión en la Unidad de Recuperación Post Anestésica en Cirugía Ambulatoria. Un reporte de caso - Céspedes Morón, Miryam Elizabeth (2021)
In recent years, the profile of patients who can undergo ambulatory surgery procedures in independent ambulatory surgical centers has changed. It is very important to consider the availability, skills and experience of the care staff, as well as the integral study of the patient, the resolution capacity of these centers and evaluations with quality care indicators to obtain optimal results. The present case was of a 34-year-old male, first presentation of rapid and symptomatic atrial fibrillation documented in the immediate postoperative period. Patient care, diagnostic strategy and treatment were described, since the patient required electrical cardioversion.